Importance of Undergraduate Research in Medical and Dental Curriculum - Laxmi Pathak; Rajeshwar Reddy Kasarla; Kripa Ghimire (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION The quality of medical education has attracted considerable interest during the last few years. This interest is especially concerned with the question of how education can be made more relevant to the needs of today’s society. Emerging changes in today’s society such as rapid advances in technology, changes in demographics, environmental factors and life style may require a revision in the present system of education in such a way that students of health profession are trained to deal with problems in the future, preparing themselves to become active, independent learners and problem-solvers, rather than more or less passive recipients of information. The recent trend in medical and dental education is introduction of undergraduate research in the medical and dental curriculum. The present article reviews and describes the importance of undergraduate research to teach students how to conduct research and to develop necessary skills that can be applied outside the academic environment, to produce competent doctors and enhance patient outcomes.